Photocatalytic thin films coupled with polymeric microcapsules for the controlled-release of volatile agents upon solar activation - Oliveira, L. Filipa (2013)
This work reports on the application of solar-activated photocatalytic thin films that allow the controlled-release of volatile agents (e.g., insecticides, repellents) from the interior of adsorbed polymeric microcapsules. In order to standardize the tests,a quantification of the inherent controlled-release of a particular volatile agent is determined by gas chromatography coupled to mass spectroscopy, so that an application can be offered to a wide range of supports from various industrial sectors, such as in textiles (clothing, curtains, mosquito nets). This technology takes advantage of the established photocatalytic property of titanium dioxide (TiO2) for the use as an active surface/site to promote the controlled-release of a specific vapor (volatile agentfrom within the aforementioned microcapsules.